Experiences of individuals using a novel web-based rehabilitation programme: Self-management Programme of Activity Coping and Education (SPACE) for chronic obstructive pulmonary disease. (2nd June 2020) - Bourne, Claire; Chaplin, Emma; Chantrell, Stacey; Singh, Sally; Apps, Lindsay
Abstract : Background/Aims: The Self-management Programme of Activity Coping and Education (SPACE) for chronic obstructive pulmonary disease has been integrated into an online programme for patients to pursue at home with the support of health care professionals. This study aimed to identify barriers and facilitators to participation in the web-based programme and to guide further development of the website. Methods: This nested qualitative study was part of a feasibility study comparing web-based rehabilitation with standard pulmonary rehabilitation. Framework analysis was performed to identify themes. Results: Four overarching themes were identified: programme content and reported gains; embedding the programme into daily routines; barriers to participating in the programme; and support. These themes describe benefits of the programme including improved activity levels, exercise intensity and knowledge of the condition, as well as the incorporation of exercise into daily routine. Both completers and non-completers acknowledged the importance of motivation and self-discipline when following the programme and that the flexibility of the programme could help or hinder engagement. Support from healthcare professionals was important and used for encouragement, to obtain health advice and technical support. Conclusions: The experiences of chronic obstructive pulmonary disease patients using this web-based rehabilitation programme illustrate how patients can benefit from such a resource and integrate it into their daily lifestyle.